دور المسؤولية الاجتماعية في تحقيق رضا الزبائن دراسة حالة- مؤسسة موبيليس وكالة الوادي - هاجر, معمير; نجوى, جنيحي; مريم, عازب الشيخ (University of eloued جامعة الوادي, 2020)
" تناولت هذه الدراسة دور المسؤولية الاجتماعية في تحقيق رضا زبائن مؤسسة موبيليس، وذلك من خلال استقصاء آراء عينة من زبائن المؤسسة في ولاية الوادي، وقد تم توزيع إستبيان على عينة عشوائية مكونة من (420) مفردة؛ حيث أظهرت نتائج هذه الدراسة وجود علاقة ذات دلالة إحصائية بين أبعاد المسؤولية الاجتماعية ورضا الزبائن وخلصت الدراسة إلى أن التزام المؤسسة بأبعاد المسؤولية الاجتماعية يؤدي إلى تحقيق رضا الزبائن. " This study dealt with the role of social responsibility in achieving the satisfaction of Mobilis customers, through a survey of the opinions of a sample of the customers of the establishment in the Wilayat of the Valley. A questionnaire was distributed to a random sample of (420) individuals; Where the results of this study showed the existence of a statistically significant relationship between the dimensions of social responsibility and customer satisfaction. The study concluded that the institution's commitment to the dimensions of social responsibility leads to achieving customer satisfaction.
مذكرة ماستر ادارة اعمال
Keywords: المسؤولية اجتماعية، المسؤولية الاجتماعية تجاه الزبائن، المسؤولية الاجتماعية تجاه المجتمع، المسؤولية الاجتماعية تجاه البيئة، رضا زبائن، مؤسسة موبيليس.; social responsibility, social responsibility towards customers, social responsibility towards society, responsibility Social towards the environment, customer satisfaction, Mobilis Corporation.